Separation of lunar daily geomagnetic variations into parts of oceanic and ionospheric origin in the Indian region - Sastri, N.S.; Rao, D.R.K. (My University, 1971)
Seasonal changes and variation in the equatorial region of the lunar semi-diurnal component in H and Z, separated into parts of oceanic and ionospheric origin by Malin's method, are examined for four Indian observatories, three in the equatorial electrojet region and one outside it. The results suggest that the amplitudes of both the oceanic and ionospheric parts in H and Z are in general smallest in the j-season. The ionospheric part in H shows equatorial enhancement. The ocean dynamo contribution is smaller than that of the ionospheric part. At Kodaikanal, an inland station about 130 km from the nearest coast, the magnitude of the oceanic part is still considerable.
Keywords: Geomagnetic variations; H-region; Z-region; Equatorial region; Lunar semi-diurnal component